Aplikasi PPDB Mandiri Online MTs Negeri 4 Gunugkidul dalam Memberikan Pelayanan pada Masyarakat - Rugiyana Rugiyana (Jurnal Pendidikan Madrasah, 2023)
This study aims to determine the development of the PPDB Mandiri Online Application in providing services to the community during the admission period of new students at MTs Negeri 4 Gunungkidul. This research uses an exploratory case study method with a qualitative approach used to obtain information on PPDB Online constraints and solutions to the development of PPDB applications. The results showed that there were several online independent PPDB application developments carried out at MTs Negeri 4 Gunungkidul, namely observation of conventional PPDB, studying the flow that can be used as digital to make it easier for prospective students to collect files and monitoring the status of registrants. Next add report card scores, achievement certificate scores and rankings. This is to bridge the obstacles experienced by prospective students in the registration process. The use of the PPDB Mandiri Online application can make it easier for students and teacher staff to know the development of the number of new students in the future.